Intervention Protocol Based on Transtheoretical Model of Behavior Change for Metabolic Syndrome - Ludwig,Martha Wallig Brusius (2021)
Abstract The present study is the translation and adaptation of an intervention based on the Transtheoretical Model of Change directed to patients at cardiovascular risk. The original 29-session manual was translated into Portuguese, extended to 36 sessions, and applied in a pilot study. The protocol was reduced to 12 sessions through the grouping based on the processes of change. The products of the present study were the processes in each behavior, the versatility of the protocol, the interdisciplinary work, the great cost-benefit, and the potential of effectiveness. Finally, the importance of consistent training in Motivational Interview, Transtheoretical Model and group management for proper use are highlighted, and the costs and benefits of protocols versus more flexible treatments are discussed.